По формуле перехода к другому основанию и свойствам логарифма:
[m]log_{\sqrt[3]{45}}25=\frac{log_{3}25}{log_{3}\sqrt[3]{45}}=\frac{log_{3}5^2}{log_{3}45^{\frac{1}{3}}}=\frac{2\cdot log_{3}5}{\frac{1}{3}log_{3}45}=\frac{2\cdot log_{3}5}{log_{3}9\cdot 5}=\frac{6\cdot log_{3}5}{log_{3}9+log_{3}5}=\frac{6\cdot log_{3}5}{2+log_{3}5}[/m]
[m]\frac{6\cdot log_{3}5}{2+log_{3}5}=q[/m] ⇒ [m] log_{3}5=\frac{q}{2}[/m]
Тогда
[m]log_{9}15=\frac{log_{3}15}{log_{3}9}=\frac{log_{3}5\cdot 3}{2}=\frac{log_{3}5+log_{3}3}{2}=\frac{\frac{q}{2}+1}{2}=[/m]... упростить